Вплив упорядкування розподiлу катiонiв у А- та октаедричних позицiях на радiацiйну стiйкiсть натрiєвих амфiболiв - Іваницький, В.П.; Литовченко, А.С.; Бондаренко, Г.Н.; Польшин, Е.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The influence of irradiation on the process of iron oxidation in structures of sodium amphiboles magnesioarfvedsonite and magnesioriebeckite is studied by the NGR-spectroscopy. It is established that magnesioarfvedsonite possesses higher radiating stability. The difference in radiating stabilities of the minerals is explained from the point of view of the octahedral cation ordering and the alkaline cation contents in the A-position.